Peran Pemberdayaan dan Kesejehteraan Keluarga (PKK) dalam Mensejahterakan Masyarakat Desa Pulo Dogom Kabupaten Labuhanbatu Utara - Yolanda Janna Aini; Simson Ginting (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
PKK (Family Welfare Empowerment) is a national movement in community development that grows from below which is managed from, by and for the community towards the realization of a family that is faithful and virtuous. The research method used in this study is a descriptive method with a qualitative approach. In researching, the researcher conducted interviews with informants from the PKK Mobilization Team of Pulo Dogom Village, the Head of Pulo Dogom Village and several people who live and live in Pulo Dogom Village. Then also carried out observation, documentation and literature study to answer research problems. To check the validity of the data, it was carried out using source triangulation techniques, technique/method triangulation and comparisons from several sources with data collection techniques such as interviews, observation and documentation as well as with related theories. The findings in the research field concluded that the Role of Empowerment and Family Welfare (PKK) in Welfare of the Communities of Pulo Dogom Village, North Labuhanbatu Regency, has not been effective and has not been maximized. The role of the PKK in Pulo Dogom Village needs to be increased due to the lack of contribution and awareness of PKK members in carrying out their responsibilities. Furthermore, the current PKK program also needs to be improved in order to achieve satisfactory results.